Community perception on safe sex, HIV/STDs and substance abuse - Rai, Shailesh; Goswami, V. P. (Public Health Review: International Journal of Public Health Research, 2018)
Background: Sexually transmitted diseases (STDs) are the problem of public health worldwide. The World Health organization reported 536 million cases of STDs all over the word, and there were 499 million people that reported the new cases of STDs. Objectives: To assess the community perception on safe sex, HIV/STDs and substance abuse. Methodology: A cross sectional observational study was carried out on 746 participants (485 male and 261 females) of reproductive age group (15-49 yr) from different localities of Indore city. Simple random selection was applied and written informed consent was obtained from the study participants. Data collected with the help of Pre-designed, Pre-tested, Semi-structured questionnaire during the period between 01 March2016 – 30 OCT 2016 and analyzed, were presented in table formats, obtained using Excel and SPSS-22. Chi square Test was applied and p value considered significant when it is < 0.05. Results: Opinion on having multiple sex partners leading to HIV/AID & STDs. 85.8% males and 83.3% females accepted the statement. About cure of HIV/AIDS, 18% males and 21.8% Femalessay yes. About safe sex,61.9% males and 57.3% females, give correct response. 45% of total 485 males smoke or take tobacco items and 23.5% take alcohol none of the females involved in this. Conclusions: Most of the study participants have knowledge about HIV transmission but somehow poor knowledge regarding its cure. Correct concept of safe sex is around 61 %. Mostly males are involved in smoking and other addiction.